MiR-29a suppresses MCF-7 cell growth by downregulating tumor necrosis factor receptor 1. Issue 2 (February 2017) - Zhao, Yiling; Yang, Fenghua; Li, Wenyuan; Xu, Chunyan; Li, Li; Chen, Lifei; Liu, Yancui; Sun, Ping
Tumor necrosis factor receptor 1 is the main receptor mediating many tumor necrosis factor-alpha–induced cellular events. Some studies have shown that tumor necrosis factor receptor 1 promotes tumorigenesis by activating nuclear factor-kappa B signaling pathway, while other studies have confirmed that tumor necrosis factor receptor 1 plays an inhibitory role in tumors growth by inducing apoptosis in breast cancer. Therefore, the function of tumor necrosis factor receptor 1 in breast cancer requires clarification. In this study, we first found that tumor necrosis factor receptor 1 was significantly increased in human breast cancer tissues and cell lines, and knockdown of tumor necrosis factor receptor 1 by small interfering RNA inhibited cell proliferation by arresting the cell cycle and inducing apoptosis. In addition, miR-29a was predicted as a regulator of tumor necrosis factor receptor 1 by TargetScan and was shown to be inversely correlated with tumor necrosis factor receptor 1 expression in human breast cancer tissues and cell lines. Luciferase reporter assay further confirmed that miR-29a negatively regulated tumor necrosis factor receptor 1 expression by binding to the 3′ untranslated region. In our functional study, miR-29a overexpression remarkably suppressed cell proliferation and colony formation, arrested the cell cycle, and induced apoptosis in MCF-7 cell. Furthermore, in combination with tumor necrosis factor receptor 1 transfection, miR-29a significantly reversed the oncogenic role caused by tumor necrosis factor receptor 1 in MCF-7 cell. In addition, we demonstrated that miR-29a suppressed MCF-7 cell growth by inactivating the nuclear factor-kappa B signaling pathway and by decreasing cyclinD1 and Bcl-2/Bax protein levels. Taken together, our results suggest that miR-29a is an important regulator of tumor necrosis factor receptor 1 expression in breast cancer and functions as a tumor suppressor by targeting tumor necrosis factor receptor 1 to influence the growth of MCF-7 cell.